2017
DOI: 10.1590/s0100-83582017350100016
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF PARTHENIUM WEED USING METABOLITES OF Alternaria japonica

Abstract: -Parthenium (Parthenium hysterophorus) is an alien invasive weed infesting many parts of the world including Pakistan. A number of herbicides have been recommended for control of this weed, but these herbicides have issues regarding human health and environmental safety. In the current study, the herbicidal potential of culture filtrates of a fungal species, namely Alternaria japonica, was evaluated against parthenium weed. The fungal species was grown in malt extract broth (MEB) and potato dextrose broth (PDB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…significantly retarded the germination of parthenium seeds up to 90%, 50% and 73%, respectively. Similarly, metabolites of Alternaria japonica and Aspergillus niger significantly reduced germination of parthenium (Javaid et al, 2017;Bashir et al, 2018). In the present study, two growth media were used for the preparation of metabolites of P. citrinum.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…significantly retarded the germination of parthenium seeds up to 90%, 50% and 73%, respectively. Similarly, metabolites of Alternaria japonica and Aspergillus niger significantly reduced germination of parthenium (Javaid et al, 2017;Bashir et al, 2018). In the present study, two growth media were used for the preparation of metabolites of P. citrinum.…”
Section: Introductionmentioning
confidence: 85%
“…One of these alternative approaches is the use of fungal metabolites either in crude form or as purified compounds (Javaid et al, 2013;Akbar and Javaid, 2013). There are various reports in which fungal metabolites successfully seized the growth of various weeds including parthenium (Javaid and Ali, 2011;Javaid et al, 2017), through the production of antifungal compounds namely holadysenterine (Akbar et al, 2014), drazepinone (Evidente et al, 2005), and ophiobolin A (Evidente et al, 2006). The herbicidal activity of various fungal species including Trichoderma, Dreschlera, Alternaria and Aspergillus against parthenium has been reported in previous literature Javaid, 2012, 2013;Javaid et al, 2013Javaid et al, , 2017Bashir et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar variable herbicidal activity was found in metabolites of Drechslera species prepared in different growth media against Rumex dentatus (Akbar andJavaid, 2010, 2013). Recently, Javaid et al (2017) reported that metabolites of Alternaria japonica prepared in malt extract broth and potato dextrose broth showed different herbicidal activities against parthenium. Variation in herbicidal activities of fungal metabolites prepared in different growth media might be associated with production of different herbicidal constituents or different quantities of the same herbicidal compound in different growth medium.…”
Section: Laboratory Bioassaysmentioning
confidence: 99%
“…showed effective control against weeds of wheat, namely Rumex dentatus, Avena fatua and Phalaris minor. Although metabolites of different fungal groups have been used as natural herbicides against parthenium (Javaid, 2010;Javaid et al, 2017), literature discussing the use of metabolites of Aspergillus niger as natural herbicide against parthenium is rare. A. niger is a fungus ubiquitous in soil that causes black mould on many fruits and vegetables, and spoils preserved foods (Stratford et al, 2016).…”
Section: Introductionmentioning
confidence: 99%